Osteopaste - a pre-clinical in vivo histological evaluation: future application - Zakaria@Mohamad, Zamzuri; Che Seman, Che Nor Zarida (2022)
Auto graft plays a vital role in promoting fusion in spinal surgery. Bone substitutes such as calcium sulphate, calcium phosphate or hydroxyapatite (HA) have osteoconductive properties, which enhance the fusion process. Osteopaste is a Malaysian-made bone substitute derived from a combination of tetracalcium phosphate (TTCP) and tri-calcium phosphate that has been designed in order to conduct a pre-clinical in vivo histological evaluation. The process was compared with the other available commercial bone substitute products. We discuss the histological results and future application of our local bone substitute product in fusion /spinal surgery.